2012
DOI: 10.1590/s1677-04202012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Cd-tolerance markers of Pfaffia glomerata (Spreng.) Pedersen plants: anatomical and physiological features

Abstract: Physiological and anatomical features of Cd-tolerance in Pfaffia glomerata were examined by exposing plantlets to nutrient solutions with increasing Cd concentrations (0, 15, 45, and 90 µmol Cd L -1 ), and possible Cd-tolerance markers were established. Cd contents were found to be higher in roots than in shoots. According to the bioconcentration factor data, this species is effectively a Cd-hyperaccumulator, as previously attested. Cd induced the appearance of xeromorphic characteristics in leaves (decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The findings suggested that the rhizosphere bacteria were crucial to the plants' ability to absorb metal in their shoots. Similar findings were made by Gomes et al, (2012) who reported that increasing Cd supply increased Pfaffia glomerata's Cd absorption. Plants use their root tissue as a defensive mechanism to shield their above-ground components from too much Cd and to prevent Cd from moving to their shoots.…”
Section: Effect Of CD and B Halotolerance On Cd Accumulation (µG /Gdw...supporting
confidence: 88%
“…The findings suggested that the rhizosphere bacteria were crucial to the plants' ability to absorb metal in their shoots. Similar findings were made by Gomes et al, (2012) who reported that increasing Cd supply increased Pfaffia glomerata's Cd absorption. Plants use their root tissue as a defensive mechanism to shield their above-ground components from too much Cd and to prevent Cd from moving to their shoots.…”
Section: Effect Of CD and B Halotolerance On Cd Accumulation (µG /Gdw...supporting
confidence: 88%
“…Studies of these responses in the leaves of tolerant Brazilian species have, however, revealed that SOD did not show any type of As-, Zn-, or Cd-inducing inhibition in the As-tolerant Anadenanthera peregrina (Gomes et al, 2013b), the Zn-tolerant Myracrodruon urundeuva (Gomes et al, 2013c), or the Cd-tolerant (and hyperaccumulator) Pfaffia glomerata (Gomes et al, 2013e) respectively; and SOD activity was always higher in treated seedlings. Increases in SOD activity have been linked to higher values of superoxide radical concentrations due to the synthesis of enzymes induced by superoxide-mediated signal transduction (Rossato et al, 2011).…”
Section: Trace Elements Tolerance In Seedlings Associated With Antioxmentioning
confidence: 93%
“…Interestingly, the addition of phosphorus to the growth substrate increased As-tolerance in A. peregrina by increasing APX activity, which decreased H 2 O 2 accumulation and helped prevent lipid peroxidation in its leaves (Gomes et al, 2013b). Similarly, P. glomerata seedlings exposed to Cd doses up to 90 mmol L 21 showed increased APX activity , or were not affected (Gomes et al, 2013e), and no growth reductions were observed under those conditions.…”
Section: Trace Elements Tolerance In Seedlings Associated With Antioxmentioning
confidence: 98%